THE INTERNATIONAL LEGAL GROUNDS FOR RECOGNIZING THE RUSSIAN FEDERATION AS A STATE-SPONSORED TERRORISM AND PUNISHMENT FOR COMMITTING THE CRIME OF AGGRESSION (AGGRESSIVE WAR) AND WAR CRIMES ON THE TERRITORY OF UKRAINE (Вісник: Міжнародні відносини, 2024)
In connection with armed aggression, violation of a range of international treaties, customary norms of international law, commission of acts of terrorism, many questions arise about the status of the state-sponsored terrorism and criminal prosecutions of the perpetrators of the offense. The purpose of this research is to examine and cover current issues of recognizing the Russian Federation as a state-sponsored terrorism and bringing to individual criminal responsibility the military-political leadership for the crime of aggression and war crimes.The research is based on such methods as analysis, synthesis, generalization and comparison, formal-logical and analytical methods.The analysis and researches of the legal grounds in international law for the recognition of the Russian Federation as a state-sponsored terrorism were carried out, along with general provisions of individual criminal responsibility for crimes against international customary law. Doctrinal approaches to granting status and a definition of the concept of "state-sponsored terrorism" were contemplated and formed respectively, the categories for granting that status are emphasized and the recognition of the Russian Federation is justified by means of the analysis of requirements and documented cases and incidents of unlawful acts committed by Russia. The provisions of the Text of the Articles on the Responsibility of States for Internationally Wrongful Acts of the ILC, the United Nations General Assembly Resolution 2625 (XXV), the International Convention for the Suppression of the Financing of Terrorism are covered, as well as the prospects for recognition as a state-sponsored terrorism by the UN Security Council and the imposition of economic sanctions.The study reveals the issues of criminal responsibility of individuals, namely the military and political leadership of the Russian Federation for the crime of aggression and combatants, other persons for war crimes. The concept of crime of aggression and war crimes is defined, the accusations of the Russian Federation of waging an aggressive war of conquest and committing war crimes in accordance with the categories and summary of the reports of independent missions of international organizations are justified and grounded.Having exemined the provisions of international legal instruments, reports and statements of international organizations that were conducted in Ukraine on the fact of unlawful actions of the Russian Federation, several practical advices on the international legal recognition of Russia as a state-sponsored terrorism was developed and the concepts of creating a special tribunal for the crime of aggression were proposed and noted the prospective of the punishment and criminal responsibility of war criminals.
Keywords: International Criminal Court, special international tribunal, individual criminal responsibility, International Humanitarian Law, war criminals, Rome Statute, terrorist acts, private military companies, sentence, Independent missions